"Layers of translation" - evidence literacy in public health practice: a qualitative secondary analysis - Wanda Martin; Joan Wharf Higgins; Bernadette (Bernie); Marjorie MacDonald (BMC, 2017)
Abstract Background Strengthening public health systems has been a concern in Canada in the wake of public health emergencies. In one Canadian province, British Columbia, a high priority has been placed on the role of evidence to guide decision making; however, there are numerous challenges to using evidence in practice. The National Collaborating Centre for Methods and Tools therefore developed the Evidence Informed Public Health Framework (EIPH), a seven step guide to assist public health practitioners to use evidence in practice. We used this framework to examine the evidence literacy of public health practitioners in BC. Methods We conducted a secondary analysis of two separate qualitative studies on the public health renewal process in which the use and understanding of evidence were key interview questions. Using constant comparative analysis, we analyzed the evidence-related data, mapping it to the categories of the EIPH framework. Results Participants require both data and evidence for multiple purposes in their daily work; data may be more important to them than research evidence. They are keen to provide evidence-based programs in which research evidence is balanced with community knowledge and local data. Practitioners recognise appraisal as an important step in using evidence, but the type of evidence most often used in daily practice does not easily lend itself to established methods for appraising research evidence. In the synthesis stage of the EIPH process, synthesized evidence in the form of systematic reviews and practice guidelines is emphasized. Participants, however, need to synthesize across the multiple forms of evidence they use and see the need for more skill and resources to help them develop skill in this type of synthesis. Conclusions Public health practitioners demonstrated a good level of evidence literacy, particularly at the collective level in the organization. The EIPH framework provides helpful guidance in how to use research evidence in practice, but it lacks support on appraising and synthesizing across the various types of evidence that practitioners consider essential in their practice. We can better support practitioners by appreciating the range of evidence they use and value and by creating tools that help them to do this.